Analisis Valuasi Ekonomi Berdasarkan Perhitungan Total Economic Value Ekosistem Mangrove Di Desa Banyuurip Kabupaten Gresik - Duwi Yunitasari; Zainuri zainuri; khiyatul masfufah (MediaTrend, 2020)
Mangrove is one of ecosystem that has potentials diversity, such as protecting shorelines and supporting fisheries in coastal areas. This study aims to determine the total economic value of mangrove forest in Banyuurip Village, Gresik Regency by using the concept of calculating economic valuation and strategy for developing mangrove ecotourism by using SWOT analysis. The total economic value was obtained from primary data by doing interview through questionnaires, and the secondary data was obtained from Banyuurip Village office. Based on the calculation of the total economic value of mangrove forest in Banyuurip Village, the result was Rp 16.059.675.381. This total economic value can be used as a reference and basis of comparison for the community and the government to determine the policy, management and utilization of existing mangrove. Furthermore, for the development of mangrove ecotourism in Banyuurip Village by using SWOT analysis.